Monitored anaesthesia care (MAC) - Laskar, M Manzoorul Hoq (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
DOI: http://dx.doi.org/10.3329/jbsa.v26i1.19807 Journal of Bangladesh Society of Anaesthesiologists 2013; 26(1): 1-3